Effect Of Rice Husk Powder On Properties Of Natural Rubber Latex Foam - Ramasamy, Shamala (2014)
Rice husk powder (RHP), an agricultural by-product incorporated into natural rubber latex (NRL) compound and foamed to produce natural rubber latex foam (NRLF) via the Dunlop method in this work. The tensile, mechanical, thermal resistance, micro structural characterization and degradation studies of RHP filled NRLF were investigated and compared with the controlled NRLF (zero RHP loading). In the first series, the effect of RHP loading from 0 to 10 phr on the properties of NRLFs was studied. In the second series, the influence of RHP size reduction was studied. The effect of partial or complete replacement of RHP with sago starch was investigated in the third series. The RHP/Sago Starch ratio was fixed to 10 phr. In the fourth series, modified RHP was used. The effects of soil burial test and exposure to natural weathering on all these samples were explored for three months in accordance to ASTM D 5247 and ISO 877.2, respectively. Result showed tensile strength, modulus at break, hardness and thermal stability increases with increasing filler loading while elongation at break and recovery percentage decreased. In second series, reduction of RHP filler size showed an improvement in the properties examined due to the enhanced RHP-matrix interaction in the NRLFS. In third series, the substitution of sago starch showed poor mechanical properties and greater thermal stability of the NRLFs. Modification of RHP reduces the lignin and silca content, thus resulting in reduced properties of NRLFs. However, these modification accelerated the degradation of RHP filled NRLFS. Deterioration in the properties of NRLFs was observed through soil burial and natural weathering test.